Bentuk Menara Phinisi UNM Makassar Terhadap Gerakan Angin dan Aliran Udara pada Lingkungan sekitarnya dengan Metode Simulasi Komputer - Usman Faharuddin (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The shape andorientationof thewind directionc an affec tthe behavior patterns of air flow around the environment and wind speeds at pedestrian level wind resulted in a complex flow pattern saround the building. While the factors that influenceis the physical topography of the building and the relation ship with the surrounding environment and other building barriers such as fences, vegetation and others. This research aimed to investigate the effectiveness of phinisi tower form against the movement patterns of wind speed and air flow occurring in the tower building and its surrounding environment using the simulation of Vasari Beta 3 software. The research method is experimental with direct measurement using the anemometer and computer simulation. The simulation was conducted to compare the tower forms with the purpose of observing the effectiveness of the tower phinisi forms againts the speed of the wind movement and the air flow pattern in the surrounding environment. The research results revealed that the phinisi tower form was very effective in resisting the movement of wind speed with simulation result value of 0.98 - 2.95 m / s in the surrounding environment, so that it meet the comfort standard in Beaufort scale 1.6 - 3.3 m / s which was effective to human.